Capitalizing Obesity - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2016)
In his 2014 article, 'Food Price Inflation as Redistribution', Joseph Baines shows the intimate correspondence between differential profit and world hunger. But the capitalization of food is a dialectical process. As Michael Harrington noted more than half a century ago in his seminal book 'The Other America', the other side of affluence is poverty; and among the American poor, the other side of hunger is overweight and obesity. Over the next fifty years, the global proportion of undernourished people has diminished while that of the obese has risen; and since the early 2000s, for the first time in history, the obese have outnumbered the undernourished. How has this remarkable hunger-to-obesity transformation evolved? What forms of capital drive the obesity epidemic, including its counter-movements of anti-obesity drugs, non-communicable disease treatments, diets, surgical fixes and psychological interventions? What are the material/ideal technologies that shift the world toward ever more destructive yet profitable forms of mass overfeeding? What policies and legislation have supported this shift, and how have they been imposed on the world's population? And most importantly, what are the qualitative and quantitative links, if any, between these various strategies of sabotage on the one hand and differential profit and capitalization on the other?
Keywords: 330; capitalization; food; hunger; obesity